The hot chick - Brady, Tom (Pasig City : Viva Video, 2003)
The hilarious Rob Schneider, has been a gigolo. He's been an animal, And now a curse will make him something he's never been before - a woman! Jessica Spencer is the hottest, most popular girl in high school. But she gets a big dose of reality when she wakes up in the body of a 30-year-old lowlife man (Schneider)! She quickly discovers that trading on your looks isn't so easy when you're a girl who constantly needs a shave. Jessica must find a way to convince her friends it really is her and somehow figure out how to change herself back into a teenage girl. From some of the guys who brought you Deuce Bigalow: Male Gigolo and The Animal comes the wild and wacky comedy everyone can enjoy - no matter what your sex.